45. Express each equation in the specified form.


a. y = (x – 3)² - 25 in standard form

B. y = 2(x – 7)(x + 3) in standard form.

C. y = - 2x² + 28x – 26 in factored form

D. y = -9x² + 72x + 81 in vertex form

2 answers

A. Y = (x-3)^2 - 25 = 0
x^2 -6x + 9 - 25 = 0
x^2 - 6x - 16 = 0.

B. y = 2(x - 7)/(x + 3) = 0.
Multiply both sides by x+3:
2(x-7) = 0,
2x - 14 = 0,
x - 7 = 0.

C. y = -2x^2 + 28x - 26 = 0,
Divide both sides by -2:
x^2 - 14x + 13 = 0,
(x - 1)(x - 13) = 0.

2x- 14 = 0.
B. Correction: y = 2(x-7)(x + 3) = 0.
Divide both sides by 2:
(x - 7)(x + 3) = 0,
x^2 - 4x - 21 = 0.